Pengaruh Level Penggunaan Jerami Padi Sebagai Absorban Terhadap Kandungan Nutrisi Silase Campuran Rumput Kume (Shorgum Plumosum Var. Timorense) dan Mucuna Bracteata - Kii, Petrus Renoldy; Oematan, Gustaf; Lestari, Gusti A. Y. (Yayasan Sumber Daya Manusia Cerdas, 2024)
This research aims to determine the effect of the level of use of rice straw as an absorbent on the nutritional content of a mixture of kume grass (Sorghum Plumosum Var. Timorense) and (Mucuna bracteata) silage. The research method is an experimental method with a Completely Randomized Design (CRD) pattern consisting of 5 treatments and 4 replications. The treatment consists of 0% rice straw + 100% kume grass + Mucuna bracteata (AJP0), 5% rice straw + 95% kume grass + Mucuna brakteata (AJP5), 10% rice straw + 90% kume grass + Mucuna bracteata (AJP10), 15% rice straw + 85% kume grass + Mucuna bracteata (AJP15), 20% rice straw + 80% kume grass + Mucuna bracteata (AJP20). The variables measured are dry matter (DW), organic matter (OM), crude protein (CP), crude fiber (CF) and crude fat (CF). The data were analyzed using analysis of variance (ANOVA) and continued with a multiple dunca distance test with the help of SPSS version 25 data processing software. The results of the analysis showed that the addition of rice straw as absorbance affected (P<0.01) and increased BK from 12.15 % to 32.37%, SK 28.42% to 35.75%. And reduced OM from 88.57% to 80.60%, CP from 15.37% to 8.22%, CF from 7.30%-5.05%. Total DW increased linearly from 12.15% (AJP0) to 32.27% (AJP20), likewise OM decreased linearly from 88.32% to 80.60% (AJP20). Likewise, CP experienced a linear decrease from 15.37% (AJP0) to 8.22% (AJP20), likewise CF experienced a linear increase from 28.42% (AJP0) to 35.75% (AJP20), as well as CF content decreased linearly from 7.30% (AJP0) to 5.05% (AJP20). Conclusion along with the use of rice straw as an absorbent in the fermentation of a mixture of fresh grass and Mucuna bracteata can increase DM, OM and CF. reducing CP and CF in silage.